Effects of Open Textbook Adoption on Teachers’ Open Practices - Mason, Stacie L; Kimmons, Royce (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
The purpose of this qualitative study was to understand whether certain theoretical benefits that open educational resources (OER) might have on teacher practice were being realized by a group of secondary teachers using open science textbooks.  In surveys and interviews, teachers were asked to describe their classroom practice before and after adopting an open textbook, including practices relating to openness.  Teachers were also asked to rate the quality of open textbooks they were using in contrast to textbooks used previously.  Most participants reported changes to practice, and the most commonly cited changes could be attributed to a combination of openness and online format.  For example, participants described linking textbook content to other online resources.  In comparisons of current to previous practice, however, teachers did not report increases in the open practices of collaboration, revising, or adapting.